Human-robot personal relationships third international conference, HRPR 2010 Leiden, the Netherlands, June 23-24, 2010 : revised selected papers - Lamers, Maarten H.; Verbeek, Fons J. (Lecture notes of the Institute for Computer Sciences, Social Informatics, and Telecommunications Engineering, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Human-Robot Personal Relationships, held in Leiden, The Netherlands, in June 2010.The 16 revised full papers presented together with 2 invited papers and 1 keynote lecture were carefully reviewed and selected from 22 submissions. The papers feature and discuss studies of personal relationships with artificial partners, their formation, their possibilities and their consequences. Such personal relationships are increasingly attracting attention from scientific fields as (social) robotics, human-computer interaction, artificial intelligence, psychology, philosophy, sociology.